2017
DOI: 10.1039/c7ra05202b
|View full text |Cite
|
Sign up to set email alerts
|

Applying rheological analysis to understand the mechanism of polyacrylamide (PAM) conditioning for sewage sludge dewatering

Abstract: Physic-chemical behavior and rheological property of PAM conditioned sludge are explored. Rheological analysis could act as a useful indicator to reveal the mechanism of sludge dewatering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…However, the FAME yields from using 4% H 2 SO 4 were 2.02 ± 0.46%, 2.08 ± 0.53%, 2.23 ± 0.50%, and 2.41 ± 0.47% in 4, 8, 16, and 24 h reaction times, respectively. For the time course experiments under different reaction time periods (4,8,16, and 24 h) with 4% H 2 SO 4 , however, results showed that there was no significant difference among the FAME yields of the three experimental sets (p > 0.05) (Figure 2b). Results showed that the highest FAME yield by acid methanolysis of sludge cake powder was with 8% H 2 SO 4 .…”
Section: Preliminary Test For Optimal Concentrations Of H 2 So 4 and mentioning
confidence: 93%
See 3 more Smart Citations
“…However, the FAME yields from using 4% H 2 SO 4 were 2.02 ± 0.46%, 2.08 ± 0.53%, 2.23 ± 0.50%, and 2.41 ± 0.47% in 4, 8, 16, and 24 h reaction times, respectively. For the time course experiments under different reaction time periods (4,8,16, and 24 h) with 4% H 2 SO 4 , however, results showed that there was no significant difference among the FAME yields of the three experimental sets (p > 0.05) (Figure 2b). Results showed that the highest FAME yield by acid methanolysis of sludge cake powder was with 8% H 2 SO 4 .…”
Section: Preliminary Test For Optimal Concentrations Of H 2 So 4 and mentioning
confidence: 93%
“…The 4 h reaction time was the optimal time period to achieve a higher accumulated FAME yield than the other reaction time periods (Figure 4b). Experimental results showed that there was no significant difference among the various reaction time periods (4,8,16, and 24 h periods) (p > 0.05) with 8% H 2 SO 4 or HCl for accumulated FAME yield (Figure 4). For stable acid methanolysis of slaughterhouse sludge cake, a stable thermostat and agitation of the sludge cake were required during the whole process.…”
Section: Acid Methanolysis Of Sludge Cake With Different Concentratiomentioning
confidence: 94%
See 2 more Smart Citations
“…Various methods of pretreatment are reported in the literature. There are usually three different ways: (1) to improve sludge settleability by coagulation or flocculation of sludge particles in the addition of polyelectrolytes, such as polyaluminium chloride, 17 ferric chloride 18 and cationic polyacrylamide; 19 (2) to improve sludge cake filterability by reducing the sludge solids compressibility in the addition of some high porous inert minerals such as fly ash, 20 gypsum, 21 wood chips and wheat dregs, 22 rice husk; 23 (3) to release the bound water from EPS by disintegration of sludge using techniques such as advanced oxidation processes (AOPs), anaerobic digestion, 15 ultrasonic, 24 electro-dewatering 7 and enzyme 25 treatment. Moreover, more researches has been undertaken to apply these pretreatments and mechanical dewatering device 6 in a number of combinations, aiming at enhancing the dewaterability at a high level.…”
Section: Introductionmentioning
confidence: 99%